2006
DOI: 10.1021/bi052132g
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of Benzyl Alcohol- and 8-Anilinonaphthalene-1-sulfonate-Induced Aggregation of Recombinant Human Interleukin-1 Receptor Antagonist

Abstract: The critical role played by temperature in ligand-induced protein aggregation was investigated. Recombinant human interleukin-1 receptor antagonist (rhIL-1ra) and the ligands benzyl alcohol and 8-anilinonaphthalene-1-sulfonate (ANS) were used. We investigated aggregation kinetics and the conformation and cysteine reactivity of rhIL-1ra in buffer alone or in the presence of 0.9% (w/v) benzyl alcohol or 4.2 or 21 mM ANS at 25 and 37 degrees C. In buffer, protein aggregation was not detected at 25 degrees C but o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
81
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(88 citation statements)
references
References 58 publications
7
81
0
Order By: Relevance
“…In a Bacillus subtilis strain, the lethal concentration of BzA increased the membrane fluidity (43). For protein structures, BzA induced the aggregation of proteins, such as human interleukin (44) and interleukin-1 receptor antagonist (45), by partially unfolding these proteins (46,47). Unfolding actions were also reported for short-chain alcohols (48).…”
Section: Discussionmentioning
confidence: 93%
“…In a Bacillus subtilis strain, the lethal concentration of BzA increased the membrane fluidity (43). For protein structures, BzA induced the aggregation of proteins, such as human interleukin (44) and interleukin-1 receptor antagonist (45), by partially unfolding these proteins (46,47). Unfolding actions were also reported for short-chain alcohols (48).…”
Section: Discussionmentioning
confidence: 93%
“…The adverse effect of benzyl alcohol was also observed during reconstitution of lyophilized rhIL1ra, where reconstitution of the dried solid with 0.9% (w/v) benzyl alcohol caused a greater degree of protein aggregation than reconstitution with water. 237 Later, Roy et al 114 found the effect of benzyl alcohol is temperature dependent. While benzyl alcohol at 0.9% accelerated aggregation of rhIL -1ra at 37 ° C (almost no monomers after 7 days), it showed no effect at 25 ° C, corresponding to temperature -dependent perturbation in the tertiary structure of rhIL -1ra in the presence of benzyl alcohol.…”
Section: Preservativesmentioning
confidence: 99%
“…Increasing the temperature slightly above room temperature may cause some proteins to aggregate on much shorter timescales. At 37 ° C, many proteins aggregate easily, including GCSF 1.0 -1.5 mg/mL at pH 7, 18,108 recombinant human keratinocyte growth factor (rhKGF) at 0.5 mg/mL at pH 7, 109 bovine insulin at pH 2.5, 110 tubulin at pH 6.4, 111 recombinant human platelet -activating factor acetylhydrolase (rhPAF -AH, pI = 6.7) after reconstitution (also at room temperature), 112 rhIL -1ra, 113,114 IgG molecules at different pH values, 61,115,116 and mutant transthyretin ( ∆ N50) at pH 7.5. 66 Other examples include aggregation of human serum albumin (HSA) at 40 ° C, 117 aggregation of fi refl y luciferase in 25 mM tricine at pH 7.5 at 42 ° C, 80 and aggregation of recombinant factor VIIa (rFVIIa) at different pH values at 45 ° C. 118 In addition to the infl uence on protein stability, higher temperature increases protein diffusion, frequencies of molecular collisions, and hydrophobic interactions, promoting protein aggregation.…”
Section: Effect Of High Temperature On Protein Aggregationmentioning
confidence: 99%
See 2 more Smart Citations